Antimicrobial activities of spices and herbs against Salmonella Oranienburg. (January 2018) - Lins, Philipp
Abstract: The detection of Salmonella spp. within dried spices and herbs is challenging due to their potent antimicrobial activity. In the present study nine condiments were investigated whereof oregano and cinnamon led to a complete inhibition of Salmonella Oranienburg at a 1:10 dilution in buffered peptone water, while towards allspice and thyme an adaptation was apparent. At a next step, a tenacity study was set up where the survival of S. Oranienburg in dry condiment samples was followed qualitatively and quantitatively during storage at 25 °C for 365 days. Generally, a higher susceptibility of S. Oranienburg to spices than herbs was determined. Furthermore, to the best of the author's knowledge, this is the first study presenting a significant antimicrobial effect of paprika/chilli against Salmonella . Nevertheless, S. Oranienburg was able to persist during storage in several condiment samples with a low reduction of log10 <1.5 colony-forming units g −1 . Thus, pointing to the outstanding ability of S. Oranienburg to survive dry storage conditions even spiked to condiments, known for their high antimicrobial activity.